2018
DOI: 10.5871/jba/006s1.375
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ownership on building sustainable and responsible businesses

Abstract: This article reviews what we know and do not know about the impact of ownership on building sustainable and responsible businesses. It begins by analysing why firm owners are an important driver of responsible business behaviour, and reviews whether such behaviour comes at a financial cost to owners or not. It then discusses how owners drive responsible business behaviour as compared to other stakeholders, reviewing the empirical evidence about the impact of different owner types on various forms of responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 79 publications
(96 reference statements)
1
17
0
Order By: Relevance
“…However, the performance of these kinds of firms cannot be measured by accounting performance ratios alone. Short and Rashid et al, (2016) also studied the relationship between ownership structure and firm performance using the market value of stock at book value and return on shareholder's equity as a measure of firm performance and they found the results to be consistent with the previous regressions by Villalonga et al,( 2018). Shahveisi et al, (2017) found empirical evidence showing that endogeneity is an issue in ownership structure.…”
Section: Literature Reviewsupporting
confidence: 59%
See 1 more Smart Citation
“…However, the performance of these kinds of firms cannot be measured by accounting performance ratios alone. Short and Rashid et al, (2016) also studied the relationship between ownership structure and firm performance using the market value of stock at book value and return on shareholder's equity as a measure of firm performance and they found the results to be consistent with the previous regressions by Villalonga et al,( 2018). Shahveisi et al, (2017) found empirical evidence showing that endogeneity is an issue in ownership structure.…”
Section: Literature Reviewsupporting
confidence: 59%
“…Shahveisi et al, (2017) found empirical evidence showing that endogeneity is an issue in ownership structure. Further evidence for the relationship between endogeneity and ownership structure was provided by Villalonga et al, (2018). Al-Malkawi et al, (2018) came up with an estimation model using a simultaneous equation employing cross-sectional data to evaluate the positive impact on Tobin's Q resulting from executive equity ownership.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous researches highlighted different approach toward the BoDs sustainability commitment depending on the ownership characteristics [93], because different owners are characterized by different goals, and time horizons being interested in longer or shorter-term investments, and different risk exposures [94][95][96][97][98].…”
Section: Internal Pressures and Related Hypothesesmentioning
confidence: 99%
“…Credible commitment to corporate purpose, therefore, requires identification of corporate ownership that promotes and supports its fulfilment (Villalonga, 2018)). An example of this, commonplace in Denmark and Germany, are ‘industrial foundations’, which are foundations and trusts that are not simply philanthropic in nature, but also own companies (Børsting and Thomsen, 2017), such as Bertelsmann, Bosch, Carlsberg, Ikea, Tata, and Velux.…”
Section: Introductionmentioning
confidence: 99%